Colorimetric Estimation of Ni(II) Ions in Aqueous Solution - S. Mathpal; N. D. Kandpal (E-Journal of Chemistry)
A rapid and accurate colorimetric method has been proposed for the estimation of nickel(II) in aqueous solution. It is found that nickel(II) ions have maximum absorbance at 393 nm in distilled water and in aqueous sucrose solution (0.3 mol dm-3). In both case, the Beer’s law was obeyed over the range from 0.04 to 0.08 mol dm -3 of nickel(II).The value of molar absorpitivity was constant 5.13±0.03 mol dm-3. This method is more rapid than the existing spectrophotometeric methods for the estimation of nickel(II). The variation in the results obtained by the method is ±2.1%.